2013
DOI: 10.1007/s12325-013-0066-8
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Glycemic Control by Re-education in Insulin Injection Technique in Patients with Diabetes Mellitus

Abstract: Re-education in the insulin injection technique led to an improvement in glycemic control in insulin-treated diabetic patients, especially in those with a poor understanding of the insulin injection technique. More attention should be paid to these strategies for outpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 23 publications
0
33
0
3
Order By: Relevance
“…Nakatani et al aimed to evaluate the impact of re-education on insulin injection technique in 87 insulin-treated patients. The results showed that there was a significant decrease in HbA1c and glycoalbumin levels in all 87 patients, with patients with a poor initial understanding of the insulin injection technique gaining the most from the re-education [19]. This study illustrates how important it is to provide proper education, including re-education, on the self-administration of insulin in order to reduce medication errors and prevent complications.…”
Section: Discussionmentioning
confidence: 98%
“…Nakatani et al aimed to evaluate the impact of re-education on insulin injection technique in 87 insulin-treated patients. The results showed that there was a significant decrease in HbA1c and glycoalbumin levels in all 87 patients, with patients with a poor initial understanding of the insulin injection technique gaining the most from the re-education [19]. This study illustrates how important it is to provide proper education, including re-education, on the self-administration of insulin in order to reduce medication errors and prevent complications.…”
Section: Discussionmentioning
confidence: 98%
“…Most Chinese patients refused insulin injection as they have the misconception that insulin injection was painful and they had needle phobia, especially in those who have never started insulin [ 23 ]. Education on insulin usage helps patients clear these kinds of misconception and allows them to accept the daily injection of insulin and improve glucose control [ 24 ]. Coupling the drop in mean HbA1c was the drop in proportion of diabetic patients solely on diet or lifestyle modification alone.…”
Section: Discussionmentioning
confidence: 99%
“…An important consideration is that many patients may require re-training on proper injection technique. Previous work observed that blood glucose control in patients displaying the poorest injection technique improved the most upon re-education [36]. This re-training helps ensure that bad habits are halted and keeps the patient up to date with the latest guideline recommendations.…”
Section: Importance Of Patient and Physician Educationmentioning
confidence: 96%